2021
DOI: 10.1016/j.jmig.2020.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Minimally Invasive Tissue Extraction in Myoma Management: A Systematic Review

Abstract: Objective: This review seeks to establish the incidence of adverse outcomes associated with minimally invasive tissue extraction at the time of surgical procedures for myomas. Data Sources: Articles published in the following databases without date restrictions: PubMed, EMBASE, Web of Science, Cochrane Database of Systematic Reviews and Trials. Search was conducted on March 25, 2020. Methods of Study Selection: Included studies evaluated minimally invasive surgical procedures for uterine myomas involving morce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 180 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Only one patient in the study group had a ULSM; it has been followed up for 24 months with no evidence of dissemination. In addition to malignancy, there is a risk of benign tissue spread after unprotected morcellation (5,18,33,34). Four cases were observed in the control group and none in the study group.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Only one patient in the study group had a ULSM; it has been followed up for 24 months with no evidence of dissemination. In addition to malignancy, there is a risk of benign tissue spread after unprotected morcellation (5,18,33,34). Four cases were observed in the control group and none in the study group.…”
Section: Discussionmentioning
confidence: 96%
“…The use of containment systems in power morcellation is accepted worldwide to thwart the spread of occult malignant tumors (5,6). However, owing to the poor compatibility between the extraction bag and the surgical instrument, the bag has a high leakage rate and is not easy to operate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bernardi's study [8] reported a significant prevalence of partially intramural, intramural with endometrium contact, and subserous fibroids. In contrast, Pepin [12] and Paul P. G. [11] found a higher occurrence of intramural myomas, while Guangping Wu's study [16] identified a combination of intramural and submucosal myomas as common.…”
Section: Prevalence and Characteristics Of Myomasmentioning
confidence: 87%
“…The average number of myomas per woman varied slightly across studies, with Bernardi, Pepin [12], and Paul P. G. [11] reporting an average of 2 myomas per woman, while Guangping Wu's study [16] observed a higher average of 3.9 myomas.…”
Section: Number Of Pregnant Women Location Of Myoma Number Of Myomas ...mentioning
confidence: 95%